Serum magnesium and proton-pump inhibitors use: a cross-sectional study - Faulhaber,Gustavo Adolpho Moreira (2013)
OBJECTIVE: The aim of this study was to evaluate the association of serum magnesium levels with proton pump inhibitors (PPIs) use and other factors. METHODS: This was a cross-sectional study of 151 patients admitted with acute diseases in the Internal Medicine Division of the Hospital de Clinicas de Porto Alegre, after the exclusion of conditions that are commonly associated with hypomagnesemia: diarrhea; vomiting; chronic alcohol use; severely uncompensated diabetes mellitus; and chronic use of laxatives, diuretics or other drugs causing magnesium deficiency. RESULTS: All patients had normal serum magnesium levels. Serum albumin and creatinine levels were positively associated with serum magnesium levels, after adjusting for confounders. There was no difference between mean serum magnesium levels of PPI users and non-users, nor between men and women; there was also no correlation among age, serum phosphorus, and potassium levels with serum magnesium levels. Limitations of this study include the absence of an instrument for measuring adherence to PPI use and the sample size. CONCLUSION: The association of PPI use and hypomagnesemia is uncommon. Congenital defects in the metabolism of magnesium may be responsible for hypomagnesemia in some patients using this drug class.